KEANEKARAGAMAN DAN DAYA DEGRADASI SELULOSA JAMUR TANAH DIHUTAN BEKAS TERBAKAR WANARISET-SEMBOJA, KALIMANTAN TIMUR - Suciatmih, Suciatmih (BERITA BIOLOGI, 2008)
In order to know the effect of isolation method on the occurrence and capability of soil fungi to degrade cellulose,a study was conducted in postburning forest in Wanariset-Semboja, East Kalimantan. Soil fungi were isolated using three isolation methods:incubation at 45° C, treatment with 50 % ethanol for 15 minutes, and heat treatment at 70° C for 15 minutes.Plates for heat incubation and for other methods were incubated at 45° C and 27° C for three days, respectively. Cellulose degradation test of isolated fungi was examined using Carboxy Methyl Cellulose (CMC) media. Results showed that isolation method affected diversity and population of soil fungi. Heat treatment at 70° C for 15 minutes appeared to have highest diversity and population of soil fungi. Eupenicillium Javanicum var javanicum (van Veyma) Stolk & Scott, Talaromyces byssoclamydoides Stolk & Samson, T. flavus(Klocker) Stolk & Samson, T. stipitatus C.R. Benjamin, and Penicillium argillaceum Stolk et al. were dominant in postburning forest in Wanariset-Semboja, East Kalimantan. Twenty-one isolated fungi degraded cellulose.